4D electrical resistivity tomography monitoring of soil moisture dynamics in an operational railway embankment. Issue 1 (1st December 2012) - Chambers, J.E.; Gunn, D.A.; Wilkinson, P.B.; Meldrum, P.I.; Haslam, E.; Holyoake, S.; Kirkham, M.; Kuras, O.; Merritt, A.; Wragg, J.
ABSTRACT: The internal moisture dynamics of an aged (> 100 years old) railway earthwork embankment, which is still in use, are investigated using 2D and 3D resistivity monitoring. A methodology was employed that included automated 3D ERT data capture and telemetric transfer with on‐site power generation, the correction of resistivity models for seasonal temperature changes and the translation of subsurface resistivity distributions into moisture content based on petrophysical relationships developed for the embankment material. Visualization of the data as 2D sections, 3D tomo‐grams and time series plots for different zones of the embankment enabled the development of seasonal wetting fronts within the embankment to be monitored at a high‐spatial resolution and the respective distributions of moisture in the flanks, crest and toes of the embankment to be assessed. Although the embankment considered here is at no immediate risk of failure, the approach developed for this study is equally applicable to other more high‐risk earthworks and natural slopes.